Reviving the shadow banking chain in Europe: Regulatory agency, technical complexity and the dynamics of co-habitation - Vanessa Endrejat; Matthias Thiemann (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
In recent years European financial regulation has experienced a tremendous reorientation with respect to the shadow banking system, which manifested first and foremost in its reframing as market-based finance. Initially identified as a source of systemic risk certain initiatives did not only fall much behind the envisaged changes but all to the contrary have been substantially modified in a way that they now aim at revitalizing these activities. The reorientation of European regulatory agency on shadow banking post-crisis, from curtailing it to facilitating resilient market-based finance, has been a cause for irritation by academic observers, dismissed by some as mere rebranding or taken as a sign of regulatory capture. All to the contrary, this paper documents the central role of regulatory agency in shadow banking's reconfiguration. It does so by analyzing the European initiatives concerning the regulation of Asset-Backed Commercial Paper (ABCP) and another prime example of shadow banking, Money Market Mutual Funds (MMFs). Based on documentary analysis and expert interviews we trace the way the recently published EU frameworks for MMFs and ABCP have been designed (in particular the STS, CRR and MMF regulation in 2017). Furthermore, we show how they have been transformed in such a way that their final versions allow to re-establish the shadow banking chain linking MMFs, the ABCP market and arguably the regular banking system. This transformation is driven by a new form of pro-active European regulatory agency which aims at creating a regulatory infrastructure able to sustain the orderly flow of real economy debt. Far from being captured by the industry, they did so consciously and in cooperation with private actors in order to maintain a channel for credit creation outside of bank credit, a task made more complicated by the rushed politicized final negotiations coupled with technical complexity. This paper thereby contributes to a new strand of literature, seeing the creation and reconfiguration of the shadow banking system as characterized by the active and conscious role of state actors.
urn:nbn:de:hebis:30:3-472343
Keywords: 330